2010
DOI: 10.1186/1472-6823-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide analogues for type 2 diabetes mellitus: systematic review and meta-analysis

Abstract: BackgroundGlucagon-like peptide (GLP-1) analogues are a new class of drugs used in the treatment of type 2 diabetes. They are given by injection, and regulate glucose levels by stimulating glucose-dependent insulin secretion and biosynthesis, suppressing glucagon secretion, and delaying gastric emptying and promoting satiety. This systematic review aims to provide evidence on the clinical effectiveness of the GLP-1 agonists in patients not achieving satisfactory glycaemic control with one or more oral glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 61 publications
4
58
0
Order By: Relevance
“…Our results were similar to previous studies, which reported that GLP-1 RAs have a significant effect on GI AEs compared with other treatments for patients with T2DM. 11,[29][30][31] Two double-blind placebo-controlled studies showed the highest dose of TAS (20 mg once weekly) was associated with higher incidences of nausea (52% and 31%) and vomiting (22% and 17.8%) than placebo. 32,33 Dose-response studies showed a dosedependent increase of nausea from EX5BID (range, 3-39%) to EX10 BID (range, 13-51%) and an increase of GI AEs from LIR0.6QD to LIR1.2QD to LIR1.8QD.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to previous studies, which reported that GLP-1 RAs have a significant effect on GI AEs compared with other treatments for patients with T2DM. 11,[29][30][31] Two double-blind placebo-controlled studies showed the highest dose of TAS (20 mg once weekly) was associated with higher incidences of nausea (52% and 31%) and vomiting (22% and 17.8%) than placebo. 32,33 Dose-response studies showed a dosedependent increase of nausea from EX5BID (range, 3-39%) to EX10 BID (range, 13-51%) and an increase of GI AEs from LIR0.6QD to LIR1.2QD to LIR1.8QD.…”
Section: Discussionmentioning
confidence: 99%
“…2 3 This concern has been heightened by an analysis of the US Food and Drug Administration adverse events database, where the spontaneous reporting rate of pancreatic cancer was 2.9 and 2.7 times higher with exenatide and sitagliptin, respectively, compared with other oral antidiabetic drugs. 4 In contrast, randomised controlled trials have not demonstrated this signal, [5][6][7][8][9][10][11] although most of these trials were of short duration and none were designed or powered to assess the risk of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon-like peptide-1 (GLP-1) is a gut hormone, secreted from the intestine in response to meal ingestion, which stimulates insulin secretion and inhibits glucagon release in a dose-dependent fashion [3]. GLP-1 can suppress appetite, food intake, decelerate gastric emptying and induce satiety, so it plays an important role in the regulation of blood glucose [4,5]. GLP-1 receptor agonists (GLP-1 RAs) include exenatide, liraglutide, albiglutide, taspoglutide, lixisenatide.…”
Section: Introductionmentioning
confidence: 99%